Newspaper advertising for public relations practitioners during the Malaya era 1957-1963 - Chang, Peng Kee; Arandas, Mohammed Fadel; Genapathy, Sivasangari; Syed Abdullah Idid, Syed Arabi (Public Relations Institute of Australia, 2020)
The very first recruitment for a public relations practitioner in Malaysia was encountered in 1948 and was advertised by the federal government of the British Colony in Malaya. This paper examines the subsequent advertisements after Malaya sought independence from the British colonial government. A total of eleven recruitment advertisements were found before the formation of Malaysia on the 16th September 1963. This paper outlines the advertisers, the titles of positions, as well as their qualifications and duties. The results show that the job requirement mainly came from the federal and local governments. Generally, the duties were related to information services and some specific responsibilities.